Mild COVID-19 induces early, quantifiable, persistent troponin I elevations in elder men - Bürgi, Justus J.; Rösslein, Matthias; Nolte, Oliver; Wick, Peter; Garcia Boy, Regine; Stranders, Siegfried; Dollenmaier, Günter; Peier, Karen; Nohynek, Brigitte; Fischer, Aldo; Stolz, Raphael; Cettuzzi, Michele; et al. (Frontiers in Cardiovascular Medicine, 2022)
Importance: Elderly patients, especially men, are at risk of increased morbidity from coronavirus disease 2019 (COVID-19). Long-term data on troponin I levels in longitudinal observational studies of outpatients with mild to moderate COVID-19 are scarce. Setting, Participants: In this cohort study, individuals with PCR-confirmed, mild to moderate SARS-CoV-2 infection as well as control individuals with confirmed negative PCR and negative SARS-CoV-2 serology were included. Study visits were performed from April 2020 through July 2021 (initialized during the first wave of the corona pandemic in Switzerland). Results: This study enrolled 278 individuals from the Canton of St. Gallen, Switzerland, aged 12 to 92 years (59.5% women) who had mild to moderate COVID-19 symptoms (outpatients only) and a diagnosis confirmed by positive RT-PCR. Fifty-four of the participants with confirmed SARS-CoV-2 infection were followed for 14 months with repeat cycles of the testing protocol. In addition, 115 symptomatic patients that were PCR and serology negative were enrolled as a control group. Low-level troponin I concentrations (cTnI) were significantly increased from baseline until week 9 after positive RT-PCR diagnosis in men older than 54 years (ΔcTnI = 5.0 ng/L (median); 95% CI 4.1 to 6.0; p = 0.02). The troponin I concentration remained elevated throughout 14 months in men older than 54 years within the cohort of 54 individuals with a prolonged observation period. This statistically significant change in troponin I concentration was not dependent on co-morbidities in this group. ALT, Creatinine, BNP and D-Dimer values after convalescence did not differ in comparison to the control cohort. Conclusion: In this exploratory analysis of individuals with confirmed SARS-CoV-2 infection, troponin I levels of men aged 54 or older significantly increased after infection. They remain elevated for at least 14 months after diagnosis. This suggest the possibility of an ongoing, long-term, low-grade, myocardial injury. Further studies with focus on elderly patients and a prolonged observational period are necessary to elucidate whether the phenomenon observed is associated with detectable structural changes to the heart muscle or is without further clinical consequences.